2019
DOI: 10.1159/000502341
|View full text |Cite
|
Sign up to set email alerts
|

NIV NAVA versus Nasal CPAP in Premature Infants: A Randomized Clinical Trial

Abstract: <b><i>Background:</i></b> Noninvasive ventilation is recommended for neonatal respiratory distress to avoid adverse effects of invasive ventilation. <b><i>Objective:</i></b> The aim of this study was to compare the feasibility of noninvasive neurally adjusted ventilatory assist (NIV NAVA) and continuous positive airway pressure (CPAP) in preterm newborn infants. <b><i>Methods:</i></b> Forty preterm infants (gestational age 28+0 to 36+6 wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 10 publications
0
30
0
2
Order By: Relevance
“…The apnea detection time used to trigger back‐up ventilation was 10 s and a shorter period may have been more appropriate in these patients 36 . Although some small randomized controlled trials 9,37 and retrospective studies 38–40 reported reduced respiratory failure rates with NIV‐NAVA, there is a lack of good evidence to determine its superiority over other modes of noninvasive support 41 . Thus, until larger randomized trials are conducted, some caution should be exercised when integrating NIV‐NAVA into the care of extremely preterm infants.…”
Section: Discussionmentioning
confidence: 99%
“…The apnea detection time used to trigger back‐up ventilation was 10 s and a shorter period may have been more appropriate in these patients 36 . Although some small randomized controlled trials 9,37 and retrospective studies 38–40 reported reduced respiratory failure rates with NIV‐NAVA, there is a lack of good evidence to determine its superiority over other modes of noninvasive support 41 . Thus, until larger randomized trials are conducted, some caution should be exercised when integrating NIV‐NAVA into the care of extremely preterm infants.…”
Section: Discussionmentioning
confidence: 99%
“…Yagui et al conducted a RCT (n = 123) comparing NIV-NAVA vs. NCPAP as the primary support in infants with BW <1500 g. There was no difference noted in the primary outcome of need for intubation prior to 72 hours of life, or for the secondary outcome of BPD, between the two groups [82]. Other small RCTs have shown that NIV-NAVA is as effective as NCPAP in preventing extubation failure, but large RCTs studying the outcome of BPD in extremely preterm infants are needed before NIV-NAVA can be routinely recommended [83][84][85][86][87].…”
Section: Non-invasive Neurally Adjusted Ventilatory Assistmentioning
confidence: 95%
“…Two recent randomized controlled studies comparing NIV‐NAVA with nasal CPAP during the early stages of RDS in moderately preterm infants, did not show any benefit in avoiding and/or time to intubation 57,58 (Table 4). Even though no difference was observed between NIV‐NAVA and nCPAP with respect to need of intubation in both these studies (35 vs. 50%, Kallio et al; 20.3 vs. 15.6%, Yagui et al), a longer duration of mechanical ventilation in the NIV‐NAVA group was reported in the study by Kallio et al, whereas a shorter duration could be observed by Yagui et al, possibly explained by surfactant being administered non‐invasively and earlier in the latter study but contradicted by the fact that NIV‐NAVA combined with early surfactant did not result in later intubation compared to nasal CPAP with early surfactant in that study 57,58 (Table 4). Using NIV‐NAVA after extubation seems more promising where two small retrospective studies observed more successful weaning with NIV‐NAVA than nCPAP, measured as failure within 72 h of extubation 59,60 .…”
Section: Neurally Adjusted Ventilatory Assistmentioning
confidence: 96%